Corporate Social Responsibility and Company Performance: The Role Of Board Characteristics - Itan, Iskandar; Giovani, Marshella; Butar-Butar, Dea Tiara Monalisa (Gorontalo Accounting Journal, 2024)
This research seeks to explore how the implementation of social responsibility practices impacts a company's performance and to investigate whether certain characteristics of the board play a moderating role in this relationship. The study collected data from 43 companies listed on the Indonesia Stock Exchange (IDX) that engaged in social responsibility activities during the period from 2017 to 2022. The analysis employed panel regression techniques. The findings of the study indicate a noteworthy negative correlation between corporate social responsibility (CSR) and return on assets (ROA). Conversely, the relationship between CSR and Tobin's Q is found to be statistically insignificant and positive. Moreover, the number of directors does not appear to moderate the relationship between CSR and company performance, whether measured by ROA or Tobin's Q. Similarly, independent commissioners do not seem to moderate the relationship between CSR and company performance when measured by ROA, but they do exhibit a moderating effect in the context of Tobin's Q.